Southeast Asian Muslim Washathyyah in the Global Era - Syahrin Harahap (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
Globalization in the world has given the huge impact on the people, as the new condition of the world has brought the world to the globalism- a consciousness and understanding that the world is one. Globalization has also unified the people in a global village that covers all aspects of life such as economic, political, cultural, religious aspects. This paper will explore the concept of wa¡a¯iyyah which stresses on the moderation and accommodative way and its implementation in Southeast Asia. The main idea of the wa¡a¯iyyah or moderation in religious life is that it offers the importance of realizing the concept of Islamic blessing for all the Universe (Islam; Ra¥matan lil ±lam³n). Therefore, the main offer of the Muslim wa¡a¯iyyah movement is to focus on developing civilization, freedom, justice, prosperity and better future for all the people. It is the main capital of the Wa¡a¯iyyah in Southeast Asia to give the significant contribution to the globalization of the world.